PRIVATIZATION OF STATE PROPERTY: ROMANIA'S EXPERIENCE AND ITS APPLICATION OPPORTUNITIES IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2025)
The article analyzes the experience of implementing an effective model of state property privatization in Romania — the investment fund "Fondul Proprietatea." It examines approaches to enterprise transformation, opening them to international investors through the fund, and attracting capital via IPO and SPO mechanisms. Furthermore, a comparison is made with the activities of the "National Investment Fund" established in Uzbekistan, and scientific-practical recommendations are provided for deepening the privatization process.